Speculative empiricism : revisiting Whitehead - Debaise, Didier (Speculative realism., 2018)
Didier Debaise focuses in on Whitehead's attempt to construct a metaphysical system of everything in the universe that exists whilst simultaneously claiming that it can account for every element of our experience, giving us a radically new way of conceiving the relations between experience and speculation.